Assessment natural radioactivity of marl as raw material at Kufa Cement Quarry in Najaf Governorate - Ali, Kamal; Awadh, Salih; Al-Auweidy, Muhanned (Iraqi Journal of Science, 2023)
This Research involves radiological study to assess the marl layer in the Euphrates Formation (Early Miocene) as a raw material for Portland cement industry. Nine wells are drilled penetrating the marl layer to the limestone beneath it. Nine samples were collected from core wells. Each sample represents one well. The concentration of the natural radionuclides 226Ra, 232Th and 40K are 14.91, 5.16 and 223.98 Bq/kg-1, respectively. They are determined by using the technique of gamma-ray spectroscopy with HPGe detector. The radiation doesn't exceed the globallypermissible limits. Then the results were compared with the reported data of other countries and with the world average activity of cement raw materials. The radium equivalent (Raeq) activities values of marl samples are lower than the limit of 370 Bq kg-1. Gamma index (Iɣ) below 1 mSv y-1. The values of the external hazard index (Hex) and the internal radiation hazard index (Hin) are less than unity. For estimating the radiological hazards on human health, these parameters are used. The results are indicated that there is no negative effect of radioactive radionuclides on workers' health.